Motif Siriah Gadang dan Bunga Anggrek Pada Kain Selendang Menggunakan Teknik Batik Tulis dan Bordir - Mutiya Wahyuni; Siti Aisyah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This final work aims to create works of written batik and embroidery art in the form of shawls by visualizing the beauty and uniqueness of the Siriah Gadang Motif and Orchid Flowers which have various types of colors as an effort to preserve Minangkabau culture, traditions and nature. The creation method for this final work is carried out in stages, namely: the preparation stage, the observation stage of the theme that the author raises, the elaboration stage (In-depth Stage), the synthetic stage (idea creation), the concept realization stage which is a follow-up stage to the completion stage of the work and finally the completion stage or Finishing Works. Based on the method used, a work in the form of a shawl with Siriah Gadang and Orchid Flower motifs was created using written batik and embroidery techniques. The author created seven works in the form of shawls with the titles: Elegance, Optimism, Softness, Happiness, Tranquility, Luxury, Luck.